Analysis of E-Marketing Mix through E-Service Quality and its Implications on Purchasing Decisions (Survey on Consumers of PT. XYZ, Tbk): Marketing Management - Munjinadir, Hafid; Solihah, Maya; Ayu Sofiati, Nunung; Sudaryo, Yoyo; Mukti Ali, Mochamad; Abdul Aziz Mubarok, Dadan; Dayona, Gurawan; Nur Sumawidjaya, Riyandi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study aims to analyze the influence of the E-Marketing Mix on E-Service Quality and its implications for Consumer Purchasing Decisions at PT. XYZ, Tbk using a quantitative approach. The population consists of 1.1 million users, with a simple random sampling technique applied to obtain 230 respondents. The results show that the E-Marketing Mix, which includes Product, Price, Place, Promotion, People, Process, and Physical Evidence, has been well implemented. E-Service Quality, consisting of Efficiency, Fulfillment, Reliability, Privacy, Responsiveness, Compensation, and Contact, is also considered satisfactory. Consumer Purchasing Decisions comprising product selection, brand choice, place, purchase timing, purchase amount, and payment method are generally good. The E-Marketing Mix has a significant influence on E-Service Quality by 59.9% and on Consumer Purchasing Decisions by 18.1%. E-Service Quality also has a significant influence on Consumer Purchasing Decisions by 35.4%. Simultaneously, the E-Marketing Mix and E-Service Quality exert a combined influence of 92.8% on Consumer Purchasing Decisions. These findings emphasize the importance of digital marketing strategies in improving service quality and consumer purchasing decisions.